New Zealand nurse migration to the United States : what makes them go? What will bring them back? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts, Nursing, Massey University, Turitea campus, New Zealand - Whittaker, Lynette (Massey University, 2013)
Within the next ten years there will be a considerable global nurse shortage and as many countries consider a variety of ways to both recruit and retain their nursing workforce, nurse migration is coming under increased scrutiny as both contributing to and solving the problem. New Zealand is a significant importer of nurses yet also loses a substantial number of its nurses to overseas positions. Within nurse migration research there are few qualitative studies that look at the reasons behind the decision to migrate and the experience of nurse migrants travelling from one developed country to another. This qualitative study utilizing an interpretive descriptive research design was employed to study the reasons why nurses leave New Zealand to work abroad, specifically to California, U.S.A. and sought also to explore what kept the nurses in the United States. Six face to face interviews were conducted. From the data, thematic analysis was employed to identify a variety of themes related to the decision to migrate, the early ‘settling in’ period, and reasons that may influence the nurses decision to remain in California. Factors identified that contributed to the nurses leaving New Zealand were the opportunity to travel while working, accessible recruitment agencies and hospitals, and past travel experiences. Adjustment difficulties in the United States were mitigated by the presence of other expatriates in close proximity, financial support from hospitals, and continual travel opportunities. Firmly ensconced in California the majority of the nurses had no immediate plans to return to New Zealand citing work and educational opportunities within the US and a favourable Californian lifestyle as primary reasons for staying. In addition the ability to retain a strong connection to their families in New Zealand through technology and frequent trips home contributed to their length of stay in the United States. Supporting family left at home was considered to be a possible reason for returning to New Zealand on a more permanent basis while a type of circular migration where the ‘best of both worlds’ could be enjoyed would also be considered by the nurses. This small study highlights the need for further research on nurses leaving and returning to New Zealand. Only by gaining a better understanding of the migrating nurse’s motivation for travel and impetus for return can health policy makers develop strategies for recruiting and retaining experienced New Zealand nurses.
Keywords: Nurse migration; Expatriate nurses; New Zealand nurses, United States; Nurse job satisfaction; Nursing supply and demand